(untitled) (Research, Society and Development, 2021)
The human relationship with domestic animals is very old, and people need the animals in their lives. There is a dynamic and mutually beneficial relationship between people and other animals, influenced by the behaviors essential to the health and well-being of both. With this growing relationship between the animal and the human being, it is important to conduct a population survey in the cities. In view of the context, the study aimed to evaluate the occurrence of canines and felines domiciled in the municipality of Pelotas, seeking to relate the factors that led to the choice of having a pet at home. For this, an online questionnaire was elaborated by Google Forms, in order to identify the occurrence of dogs and or cats in the municipality of Pelotas - RS. The presence of pets at home is present in the homes of 236 (86.4%) of the people who responded. we can observe that the presence of cats in the homes of the city of Pelotas - RS reaches 28% when we analyze the responses of people has a cat at least, showing the tendency of increasing the number of cats in relation to the number of dogs. The adoption of pets was given with the preference for tutors, as a way to have a pet at home. In addition, there is a tendency that pets are occupying a place within the family, since many live alone and he becomes a friend and even a son.